BENDEL KESLINGMAS NO 124 TAHUN 2014 - Apry, Wildan, Muhammad, unike dan kawan- kawan (Buletin Keslingmas, 2014)
Abstract  Hambawang mango categorized as relatively perishable fruit (rotten). This is because the water content in the mango fruit which is quite high, it made. The hambawang mango preservation was done by using a sugar solution preservation system. The research objective was determining the effect of various sugar concentration of in the preservation process to the hambawang mangoes durability. The research design used was quasi experiment. The research sample was fresh hambawang mango (without seeds), washed, soaked in a salt and whiting solution, boiling mango fruit, sugar solution sauce making, mixing with the sauce and stir it well, soaking hambawang mango fruit and store in a 1,200 milliliters jar weighing 1000 grams per milliliters solution. Sugar concentration studied were 0%, 25%,30%, 35%,40%,and 45%. Based on the Kruskal-Wallis test results at 0.05significance level, obtained significant value of 0.000 0.05, it concluded that there are aignifficant differences among various sugar concentration solution in the wet preservation system process of hambawang mango sweetmeat making durability and continued with Mann-Whitney test the result shows that there was signifficant difference among various sugar solution concentrations. Hambawang mango sweetmeat preservation durability on 0% sugar concentration (as a control) was 1.7 days; 25%concentration for 3 days; 30%concentration for 4.4 days; 35% concentration for 5.6 days; 40% concentration for 7 days; 45% concentration for 8.7 days. The greater the sugar concentration the durability will be longer. The proposed suggestion for future researchers can continue this research with various sample type, sample number, and various sugar solution concentration.